{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Equating order frequencies we have found set to

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: es to F = mv 2 /R, as it should. R2 (xx + y y ) + (xy − y x)2 = 0. ¨ ¨ ˙ ˙ (320) 6.39. Bead on stick, using F = ma Using mx = F (x/R) and my = −mg + F (y/R) to eliminate the x and y in Eq. ¨ ¨ ¨ ¨ (320) gives (a) There is no force in the r direction, so the first of Eqs. (3.51) gives (using ˙ θ = ω ) r = rω 2 . Multiplying through by r and integrating yields ¨ ˙ Fy Fx R2 x +y −g + (xy − y x)2 = 0 ˙ ˙ 12 1 1 1 mR mR rr dt = ω 2 ¨˙ rr dt =⇒ ˙ r = r2 ω 2 + C =⇒ ˙ mr2 − mr2 ω 2 = E, ˙ 2 2 2 2 y m =⇒ F = mg − 3 (xy − y x)2 . ˙ ˙ (321)(328) R R where E ≡ mC is a constant of integration. ˙ ˙ Finally, using x = R sin θ =⇒ x = Rθ cos θ, and y = R cos θ =⇒ y = −Rθ sin θ, ˙ ˙ ¨ ˙ (b) Since θ θ −0, the2second of Eqs. (3.51) gives (using θ = ω ) Fθ = 2mω r. So the ˙ ˙ gives F = mg cos = mRθ , as desired. work done on the bead is θ W= t (2mω r)r(ω dt) = mr2 ω 2 ˙ F θ ( r dθ ) = θ0 r . (329) r0 t0 Since W = ∆K = K − K0 , the kinetic energy is 2 K = K0 + W = K0 + mr2 ω 2 − mr0 ω 2 ≡ mr2 ω 2 +...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online